Structured Object-Oriented Formal Language and Method Second International Workshop, SOFL 2012, Kyoto, Japan, November 13, 2012. Revised Selected Papers - Liu, Shaoying; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Workshop on Structured Object-Oriented Formal Language, SOFL 2012, held in Kyoto, Japan, in November 2012. The 10 full papers presented were carefully reviewed and selected for inclusion in this book and address the following topics of interest: testing and tools; tools for specification; model checking; and application and prototyping.
Testing and tools -- Tools for specification -- Model checking -- Application and prototyping.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Computer Science; Logics and Meanings of Programs; Software Engineering; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages; Programming Techniques; Computer Communication Networks